2004
DOI: 10.1023/b:catl.0000029521.80714.8d
|View full text |Cite
|
Sign up to set email alerts
|

Potential of UV–Raman Spectroscopy for Characterization of Sub-monolayer MoOxModel Catalysts at Ambient Pressure

Abstract: UV-Raman spectroscopy is demonstrated to be a valuable tool to study molybdenumoxide model catalysts at ambient pressure while visible light Raman yields no information. UV-Raman offers the possibility to characterize MoO x /Al 2 O 3 /Si and MoO x /SiO 2 / Si model systems with sub-monolayer loading of MoO x even though the surface area of a Si-wafer is much lower than that of a bulk support. Anchoring of MoO x onto Al 2 O 3 /Si and SiO 2 /Si results in similar molybdenum oxide compounds as for bulk catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The two sharp features at 1557 and 2334 cm –1 originate from gas-phase molecular oxygen and nitrogen, respectively. , For the weakly loaded samples, the oxygen feature also exhibits some rotational fine structure . Besides, substrate features due to crystalline silicon are detected at 512 and ∼940 cm –1 . ,, In particular, the peak at 512 cm –1 , which is slightly red-shifted due to the sample temperature, corresponds to a Si–Si stretching mode, while the broad band at ∼940 cm –1 is assigned to the Si overtone region…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The two sharp features at 1557 and 2334 cm –1 originate from gas-phase molecular oxygen and nitrogen, respectively. , For the weakly loaded samples, the oxygen feature also exhibits some rotational fine structure . Besides, substrate features due to crystalline silicon are detected at 512 and ∼940 cm –1 . ,, In particular, the peak at 512 cm –1 , which is slightly red-shifted due to the sample temperature, corresponds to a Si–Si stretching mode, while the broad band at ∼940 cm –1 is assigned to the Si overtone region…”
Section: Resultsmentioning
confidence: 96%
“…Such an approach is beneficial when studying specific structural aspects, as in this work. While we are not aware of any Raman studies on such planar vanadia systems, Mojet et al investigated similar model systems for dispersed molybdena using UV Raman spectroscopy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that the bands corresponding to the Mo-O-Mo links increased proportionally when increasing the bands corresponding to the MoO 2t links [2,41,43]. This suggests that there was an increase in the number of bridges of Mo, which implied high dispersion of Mo on the support [40,44]. Additionally, bands between 905 and 918 cm −1 for the C5 and CoMoind catalysts were attributed to the presence of molybdate CoMoO 4 species, either isolated or polymerized, involving a strong interaction with the support.…”
Section: Raman Analysismentioning
confidence: 94%
“…For C1 and C2 catalysts, a band in the range between 970 and 1100 cm −1 was detected and highly dispersed MoO 4 tetrahedral species can be assigned in agreement with MAS-NMR results. It is likely that these metal loadings did not reach the MoOx monolayer formation [44,47]. Moreover, the bands appearing between 200 and 400 cm −1 were attributed to Mo monomeric species [33].…”
Section: Raman Analysismentioning
confidence: 99%